If conditional structures expressing politeness strategies: a corpus-based research on english and american press discourse - Võ Thị Thanh Trúc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study aims at investigating If Conditional Structures expressing politeness through corpus-based approach. The study is also aimed at finding the differences and similarities in the language of expressing politeness between English and American Press in terms of politeness strategies. The study’s findings are expected to contribute to the better understanding of politeness expressions, how to save theirs and other party’s face and to use these strategies in communication effectively by writing politely